The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0885328218757064
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of a PLCL fibrous scaffold for soft tissue engineering applications: A combined biological and mechanical characterisation

Abstract: Poly(lactide-co-ε-caprolactone) (PLCL) has been reported to be a good candidate for tissue engineering because of its good biocompatibility. Particularly, a braided PLCL scaffold (PLL/PCL ratio = 85/15) has been recently designed and partially validated for ligament tissue engineering. In the present study, we assessed the in vivo biocompatibility of acellular and cellularised scaffolds in a rat model. We then determined its in vitro biocompatibility using stem cells issued from both bone marrow and Wharton Je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 59 publications
0
22
0
2
Order By: Relevance
“…Blends of PCL/natural polymers met the mechanical properties such as elasticity, reversible elongation and energy absorbed up to the elastic point reported for the basement membrane in the alveolar region. Other synthetic polymers such as P(LLA‐CL) also showed appropriate mechanical properties for soft tissue applications . For instance, electrospun hybrid scaffolds of collagen/P(LLA‐CL) has been used for application of cardiovascular tissue engineering .…”
Section: Future Directions: Biomimetic Models Of the Lungmentioning
confidence: 99%
“…Blends of PCL/natural polymers met the mechanical properties such as elasticity, reversible elongation and energy absorbed up to the elastic point reported for the basement membrane in the alveolar region. Other synthetic polymers such as P(LLA‐CL) also showed appropriate mechanical properties for soft tissue applications . For instance, electrospun hybrid scaffolds of collagen/P(LLA‐CL) has been used for application of cardiovascular tissue engineering .…”
Section: Future Directions: Biomimetic Models Of the Lungmentioning
confidence: 99%
“…As far our knowledge goes, there are no similar published studies on hydrolytic degradation of PLA. Previous works considered the whole stress-strain curve but discarded the strain rate effects [37][38][39].…”
Section: Effect Of Hydrolytic Degradation On the Mechanical Propertiesmentioning
confidence: 99%
“…The cell proliferation and migration as well as the extracellular matrix synthesis were promoted, indicating a strong potential for ligament regeneration. However, in the same study we had also observed a premature risk of mechanical failure in the first weeks of implantation due to PLCL [ 16 ]. On the contrary, silk was reported to degrade in more than one year, which may not coordinate with the neo-tissue development rate.…”
Section: Discussionmentioning
confidence: 95%
“…In our previous study [ 15 ], PLCL (poly-( l -lactide- co -ε-caprolactone)) has been used to construct a multilayer braided scaffold for tissue engineering application. The PLCL scaffold showed satisfying initial mechanical properties and biocompatibility, and encouraged the adhesion, migration, proliferation of cells as well as tissue regeneration [ 15 , 16 ]. Moreover, this scaffold exhibited high flexibility and tunable elasticity, showing potential application towards ligament regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation